2008
DOI: 10.2478/v10019-008-0006-4
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine cathepsins and stefins in head and neck cancer: an update of clinical studies

Abstract: tract, major salivary glands and nodes from the neck. The majority of tumors is of squamous cell origin and alcohol and tobacco abuse are the two most important etiological factors. Surgery and radiotherapy are standard treatment options with systemic therapy being added to irradiation of the patients with increased risk for disease recurrence. 1 To distinguish biologically more aggressive and less aggressive head and neck carcinomas within each traditional risk-category, numerous new prognostic factors were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Presumably, cathepsins are involved in the initial steps of a proteolytic cascade45, leading to pericellular proteolysis, although alternative pathways of migration and interplay of proteases and inhibitors are possible 18,46,47. In high grade tumours higher expression of Cats B and S has been mostly linked to tumour invasion 18,19,22,30,48. We recently reported higher levels of all three Cats in invading than in non-invading cells separated from collagen embedded U87-MG spheroids, however only increased activation of CatB contributed to higher invasion 25.…”
Section: Discussionmentioning
confidence: 91%
“…Presumably, cathepsins are involved in the initial steps of a proteolytic cascade45, leading to pericellular proteolysis, although alternative pathways of migration and interplay of proteases and inhibitors are possible 18,46,47. In high grade tumours higher expression of Cats B and S has been mostly linked to tumour invasion 18,19,22,30,48. We recently reported higher levels of all three Cats in invading than in non-invading cells separated from collagen embedded U87-MG spheroids, however only increased activation of CatB contributed to higher invasion 25.…”
Section: Discussionmentioning
confidence: 91%
“…Hypofolatemia and metabolic alteration in homocysteine, vitamin B12 could be associated with laryngeal cancer 63. Therefore, a great effort was made to proof this association as it was made to find association between cysteine cathepsins as well as stefins and promoting and invasion of head and neck tumours 63,64. Increased plasma vitamin B12 concentration may reduce the risk of rectal cancer 65…”
Section: B Vitamins For Cancer Preventionmentioning
confidence: 99%
“…Nieto et al showed in their study that BMI lower than 22 for smokers and drinkers significantly increases odds ratio for developing oral cancer. 70 Since alcohol and tobacco abuse are the two most important etiological factors for OSSC 71 , only 2 of our patients were nonsmokers and all admitted to drinking modestly. We decided to check BMI regularly in OSCC patients because of the known fact that cachexia-anorexia syndrome occurs in 30 to 80% of cancer patients.…”
Section: Discussionmentioning
confidence: 99%